Inflation targeting in the UK monetary policy framework - Eddie George (Bank of Finland, 1995)
Governor of the Bank of England presented the following paper at a seminar held at the Bank of Finland on 27 March 1995.The paper discusses monetary policy targeting in the United Kingdom, with special reference to the inflation target and the experiences gained from it.
URN:NBN:fi:bof-20140807380
Keywords: 330